Inhibition of caspases primes colon cancer cells for 5-fluorouracil-induced TNF-α-dependent necroptosis driven by RIP1 kinase and NF-[kappa]B - Oliver Metzig, Marie; Fuchs, Dominik; Tagscherer, Katrin; Gröne, Hermann-Josef; Schirmacher, Peter; Roth, Wilfried (Oncogene, 2016)
Resistance towards the drug 5-fluorouracil (5-FU) is a key challenge in the adjuvant chemotherapy of colorectal cancer (CRC), and novel targeted approaches are required to improve the therapeutic outcome. Necroptosis is a recently discovered form of programmed cell death, which depends on receptor interacting protein 1 (RIP1) and particularly occurs under caspase-deficient conditions. The targeted induction of necroptosis represents a promising strategy to overcome apoptosis resistance in cancer. The aim of this study was to systematically explore the usage of pan-caspase inhibitors to sensitize resistant CRC cells for 5-FU. We found that pan-caspase inhibitors facilitated 5-FU-induced necroptosis, which was mediated by autocrine secretion of tumor necrosis factor α (TNF-α). TNF-α production was driven by nuclear factor κB (NF-κB) and required RIP1 kinase. In vivo xenograft experiments showed that the novel pan-caspase inhibitor IDN-7314 in combination with 5-FU synergistically blocked tumor growth. Ex vivo experiments with fresh human CRC tissue specimens further indicated that a subgroup of patients could benefit from combinatory treatment. Thereby, elevated levels of secreted TNF-α and expression of components of the necroptotic pathway might help to predict the sensitivity to pro-necroptotic therapies. Together, our results shed new light on the molecular regulation of necroptosis by NF-κB and RIP1. Moreover, we identify necroptotic cell death as an important effector mechanism of 5-FU-mediated anti-tumoral activity. On the basis of this study, we propose pan-caspase inhibitors as a novel approach in the adjuvant chemotherapy of CRC.
Published online 2 November 2015
Im Titel ist "kappa" als griechischer Buchstaben dargestellt
Gesehen am 04.05.2020